The Influence of Block Games and Coconut Shell Clogs on Students’ Physical Fitness in Learning Physical Education, Sports, and Health - AR, Nazom Nurhawi; Rosani, Meilia; Akhbar, M Taheri (Journal of Social Work and Science Education, 2023)
The purpose of this study was the effect of the game hadang and Tempurung Bakiak on the physical fitness of students in learning physical education, sports, and health at SMP Negeri 27 Palembang. This research was conducted at SMP Negeri 27 Palembang which is located on Jl. Rejung No. 198, Sako Baru, Kec. Sako, Palembang City, South Sumatra 30961. The method used in this study is an experimental method with a pre-test and post-test one group design. The data collection technique used the bleed test technique or a 20-meter back-and-forth test. The population of this study were all students of class VIII at SMP Negeri 27 Palembang, while there were students in class VIII.2 and VIII.3 with a total of 65 people. The data analysis technique used is the inferential data analysis technique with the help of the t test SPSS version 23.00 for windows. Based on the discussion that has been stated above, it can be concluded that: (1) there is an effect of obstacle games on students’ physical fitness in learning physical education, sports, and health; (2) The Effect of Playing Coconut Shell Clogs on Students’ Physical Fitness in Learning Physical Education, Sports, and Health.